Praise of failure (XXI Century. Spanish Literature and Culture, 2012)
In In Praise of Failure the writer Angel Vallecillo reflects upon the creative process from a different perspective: the author´s frustration when he faces  the abysmal gap between the limitations of language and the freedom of his own imagination. To illustrate this gap he refers to “liquid” and “solid” literature, to distinguish between the literature that dwells in the imagination and literature in the written page. He also distinguishes between voluntary and involuntary imagination. Vallecillo is the author of innovative essays such as Breakdowns or There are One Million Races.  In the present work, In Praise of Failure, he focuses on the mental process prior to writing and thus discloses to the reader the inner workings of a creative imagination.
Keywords: Ángel Vallecillo; Creation; Imagination; Language